The Influence of Public Service Justice in Complaint Handling at the Secretariat General of DPR RI - Arifin Fajar Putera; Ayu Amalia; Shanty Irma Idrus (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Public complaints play a critical role in providing feedback on service delivery, enabling institutions to enhance performance, promote accountability, and uphold social justice. This study examines the influence of perceived justice in complaint handling on public satisfaction within the Secretariat General of the House of Representatives of the Republic of Indonesia (DPR RI). Adopting a quantitative approach, data were collected from 258 respondents—comprising civil servants, private-sector employees, professionals, NGO workers, and the general public—using a Likert-scale questionnaire distributed via Google Forms. This research focuses on three dimensions of justice: distributive, procedural, and interactional. The findings indicate that interactional justice—encompassing respectful treatment, clear communication, and ethical behavior—has the strongest impact on public satisfaction. These results underscore the importance of interpersonal engagement during the complaint resolution process as a key factor in shaping public trust and improving institutional image. The novelty of this study lies in its comprehensive analysis of justice perceptions in the context of a legislative institution’s complaint management system—an area that has been relatively underexplored in prior research. Unlike existing studies that primarily focus on executive or frontline service agencies, this study provides new insights into how justice-based approaches in legislative complaint handling can enhance public service responsiveness, transparency, and credibility.